Production and characterization of craft beers with different additions of native fruits and agro-industrial residues: a review - Admilson Costa da Cunha; Natália Drumond Lopes; Milene Teixeira Barcia; Cláudia Kaehler Sautter; Cristiano Augusto Ballus (Ciência Rural, 2023)
ABSTRACT: There is a growing demand for authentic products that provide sensory characteristics combined with health benefits that current studies have focused on. This review addressed the technological aspects involved in producing craft beers and the use of various fruits in developing new products with higher added value. The information was collected by researching scientific databases such as Scopus, websites, and the CAPES catalog of Theses and Dissertations. Thus, this study sought to obtain more information to promote discussion about the possibilities of adding various fruits in developing beers with a strong cultural appeal, high nutritional and marketing value, and that can also be categorized as a functional food.